Az Erzsébet Tudományegyetem pécsi épületei - Pilkhoffer, Mónika (Per Aspera ad Astra, 2014)
Founded in 1912, the Erzsébet University of Pozsony found its home in Pécs following the disintegration of historic Hungary. In 1921, shortly after the Serbian occupation of the town ended, the only way the university could find a home was to have buildings donated to the institute. As the cadet academy, the only big enough structure, was not available, the faculties, institutes and clinics of the university began operations in 1923 in buildings located in 19 different points around town. The clinics of the university found appropriate housing thanks to the numerous medical institutes of the town, but the theoretical institutes, especially the faculties of law and humanities were constantly lacking sufficient space. The period between the two world wars did not see such large scale university investments as those in Szeged or Debrecen, but a few new structures were built: in 1929 the Szent Mór College was consecrated, in 1931 the teachers’ living quarters was erected, and by 1934 the new faculty of law building and in 1939 the gymnasium were completed. Although the idea of a joint campus has emerged a few times, the buildings of the university are still scattered around Pécs to this day. (Translated by Ágnes Lengvári) Fotó: Magyar Nemzeti Levéltár Baranya Megyei Levéltára